Personagens na fronteira : a perspectiva decolonial da conquiata em Carlos Fuentes e Carmen Boullosa - Silva, Luciana Delgado da (2022)
This study proposes a reflection on the role of the literature that, in the final decade of the 20th century, revisits the historiography of the conquest of America aiming at a reconfiguration of historical characters mythified by hegemonic discourse, constituting the basis of our Latin American identities. The general objective here is to discuss the function of literary discourse in the continental decolonization project, through the investigation of its connection with the deconstruction of a colonial imaginary of inferiority and/or exclusion of Latin American voices in canonical discursive contexts. The corpus of this bibliographic research is constituted by the works of two Mexican writers: El Naranjo, by Carlos Fuentes, and Llanto, by Carmen Boullosa, both sharing the interest in the theme; the proximity of the publication date, which surrounds the ambiguous celebration of the fifth centenary of the Spanish invasion; and the choice for foundational myths, brought as protagonists of their literary reinterpretations. The theoretical body of this research relies on the contribution of decolonial studies' analysis of coloniality. Some concepts of the dialogic theory of discourse, based on the work carried out by the Bakhtin Circle, are articulated in the analysis of the works. Fuentes shows the clash between the heirs and also the associates of the conquistador Hernán Cortés, bringing subjective memories in the reconstruction of that historical event. The author also deconstructs the Colombian utopia, parodied in an ironic and dystopian future. Boullosa reevokes a Moctezuma lost in incomprehension facing the end, reclaiming his right to narrate from his failure to his infamous death. The Boullosian writing challenges itself to the task of recovering an ignored collective memory, of the countless and anonymous Indigenous women, repeatedly humiliated and despised by the powerful and the writers. The dialogue between the literary and the historical narrative updates the past under the critical eye of the present, which leads to the transformation of political-social relations, bringing winds of change in the politics of memories experienced by characters on the border, inscribed in the colonial difference.